Updates to the RIFM Criteria Document for fragrance ingredient evaluation - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Temperature, taphonomy, or technique? Contrasting hypotheses of ancient DNA recovery from Quaternary asphaltic fossil deposits - Robin R. Singleton; Kristen M. Rayfield; Karissa S. Hughes; Ezra M. Flint; Karin A. Rice; Laura R. Tewksbury; Sean C. Campbell; Aisling B. Farrell; John R. Southon; Emily L. Lindsey; Courtney A. Hofman; Alexis M. Mychajliw (Quaternary Science Reviews, 2026)

Update to RIFM fragrance ingredient safety assessment, 2-propanol, 1,1′,1′,1'-(1,2-ethanediyldinitrilo)tetrakis-, CAS Registry Number 102-60-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, octyl crotonate, CAS Registry Number 22874-79-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, propenylguaethol, CAS Registry Number 94-86-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, ethyl 3-hydroxybutyrate, CAS Registry Number 5405-41-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 3-(p-tert-butylphenyl)-2-methylpropanol, CAS Registry Number 56107-04-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, ethyl 3-hydroxyhexanoate, CAS Registry Number 2305-25-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, linoleic acid, CAS Registry Number 60-33-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, β-naphthyl isobutyl ether, CAS Registry Number 2173-57-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 1,5-dimethylhexyl acetate, CAS Registry Number 67952-57-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 3-(4-methyl-3-pentenyl)-3-cyclohexene-1-carbonitrile, CAS Registry Number 68084-04-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, cyclohexaneethyl acetate, CAS Registry Number 21722-83-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, 3,5,5-trimethylcyclohexanol, CAS Registry Number 116-02-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, 5-methyl-2-phenyl-2-hexenal, CAS Registry Number 21834-92-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 4-heptanol, 2,6-dimethyl-,acetate, CAS Registry Number 10250-45-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, phenylacetaldehyde glyceryl acetal, CAS Registry Number 29895-73-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, cyclohexanemethanol, 2,4-dimethyl-, CAS Registry Number 68480-15-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 2,2,6-trimethylcyclohexanone, CAS Registry Number 2408-37-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, cis-4-(isopropyl)cyclohexanemethanol, CAS registry number 13828-37-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, cyclohexanone, 2-ethyl-4,4-dimethyl-, CAS registry number 55739-89-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, squalene, CAS Registry Number 111-02-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, β-guaiene, CAS Registry Number 88-84-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, 3-hexene, 1,1′,''-[ethylidynestris(oxy)]tris-, (3Z, 3′Z,3"Z)-, CAS registry number 215305-10-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, methyl 3-hydroxyhexanoate, CAS Registry Number 21188-58-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, 4-methyl-2-phenyl-2-pentenal, CAS Registry Number 26643-91-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, 2-phenyl-2-butenal, CAS Registry Number 4411-89-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, dodecyldimethylamine oxide, CAS Registry Number 1643-20-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, tricosane, CAS Registry Number 638-67-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, methyl 2-nonenoate, CAS registry number 111-79-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 4-(isopropyl)-β-methylcyclohexanethanol, CAS Registry Number 67634-03-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, undecanol, CAS Registry Number 30207-98-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, methyl cis-5-octenoate, CAS Registry Number 41654-15-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, methyl 3-nonenoate, CAS Registry Number 13481-87-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 4-methyl-3-penten-2-one, CAS Registry Number 141-79-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, methyl 3-hexenoate, CAS Registry Number 2396-78-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Corrigendum to “Temperature, taphonomy, or technique? Contrasting hypotheses of ancient DNA recovery from Quaternary asphaltic fossil deposits” [Quat. Sci. Rev. 389 (2026) 110106] - Robin Singleton; Kristen M. Rayfield; Karissa S. Hughes; Ezra M. Flint; Karin A. Rice; Laura R. Tewksbury; Sean C. Campbell; Aisling B. Farrell; John R. Southon; Emily L. Lindsey; Courtney A. Hofman; Alexis M. Mychajliw (Quaternary Science Reviews, 2026)

Infalling ring material produce layers of charged dust in the ionosphere of Saturn - J.-E. Wahlund; E. Vigren; J. Dreyer; M.W. Morooka; S. Buchert; A.I. Eriksson; O. Shebanits; J. Gumbel; L. Megner; W.M. Farrell; W.S. Kurth; J.H. Waite (Icarus, 2026)

Floodplain-lake hydroperiod modulates the response of zooplankton and phytoplankton resting stages to extreme droughts - G. Chaparro; I. O’Farrell; N. S. Morandeira; M. P. Gayol (Hydrobiologia, 2026)

United States comprehensive cancer control plans: a national review - Leslie S. Given; Karin Hohman; Cynthia Vinson; Nikki Hayes; Beth Slotman; Lisa Stevens; Prajakta Adsul; Kalina Duncan; Margaret Farrell; Aubrey Villalobos (Cancer Causes & Control, 2026)

RIFM fragrance ingredient safety assessment, 1-(1,2,3,4,5,6,7,8-octahydro-2,3,8,8-tetramethyl-2-naphthalenyl)ethanone, CAS Registry Number 54464-57-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, docosane, CAS Registry Number 629-97-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, methyl jasmonate, CAS Registry Number 1211-29-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 2-isobutyl-4-methyltetrahydro-2H-pyran-4-ol, CAS Registry Number 63500-71-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, dimyrcene, CAS Registry Number 532-87-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, methyl myristate, CAS Registry Number 124-10-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, cyclohexane, 1-ethenyl-1-methyl-2,4-bis(1-methylethenyl)-, (1R,2R,4S)-rel-, CAS Registry Number 33880-83-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, ethyl myristate, CAS Registry Number 124-06-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 2-methylpentyl 2-methylvalerate, CAS Registry Number 90397-38-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, pyrazine, methyl (methylthio)-, CAS Registry Number 67952-65-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, 2-propenoic acid, 2-[1-(3,3-dimethylcyclohexyl)ethoxy]-2-methylpropyl ester, CAS Registry Number 820975-49-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, hexadecyl palmitate, CAS Registry Number 540-10-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, cyclohexane, 1-ethenyl-1-methyl-2-(1-methylethenyl)-4-(1-methylethyl)-, didehydro derivative, CAS Registry Number 68845-33-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, acetyl cedrene, CAS Registry Number 32388-55-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, butyl sulfide, CAS Registry Number 544-40-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, heneicosane, CAS Registry Number 629-94-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, ethyl palmitate, CAS Registry Number 628-97-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, sclareol, CAS registry number 515-03-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, ethyl octadecanoate, CAS Registry Number 111-61-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, cyclohexyl methyl pentanone, CAS Registry Number 4927-39-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, heptadecane, CAS Registry Number 629-78-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, hexadecane, CAS Registry Number 544-76-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, oleic acid, CAS Registry Number 112-80-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, pentadecane, CAS Registry Number 629-62-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, tetradecane, CAS Registry Number 629-59-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, nonadecane, CAS Registry Number 629-92-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, octadecane, CAS Registry Number 593-45-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, eicosane, CAS Registry Number 112-95-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessments, ethyl ricinoleate, CAS Registry Number 55066-53-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, 4-methyl-8-methylenetricyclo[3.3.1.(3,7)]decan-2-yl acetate, CAS Registry Number 122760-85-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Promoting Research Excellence in Down Syndrome: Proceedings of the 5th International Conference of the Trisomy 21 Research Society - Fabio Di Domenico; Marzia Perluigi; Antonella Tramutola; Maria Giulia Bacalini; Daniella Balduino Victorino; Isabel Barroeta; Renata Bartesaghi; Angelo Carfi; Maria Carmona-Iragui; Ann D. Cohen; Alberto C. S. Costa; Floriana Costanzo; et al. (NeuroMolecular Medicine, 2026)
Down syndrome (DS), or trisomy 21 (T21), represents the most common genetic cause of intellectual disability worldwide and is associated with a wide range of medical, developmental, and neurodegenerative conditions, including a universal predisposition to early-onset Alzheimer’s disease (AD). Since its establishment in 2014, the Trisomy 21 Research Society (T21RS) has provided a global forum for advancing DS research across disciplines and promoting translational efforts to improve health and quality of life. Every two years, T21RS hosts an international scientific meeting that brings together researchers, clinicians, self-advocates, families, and industry stakeholders. In 2024, the 5th T21RS International Conference was held in Rome, Italy, from June 5 to 8, under the theme “Promoting Research Excellence in Down Syndrome.” The meeting brought together about 500 scientists from 26 countries across five continents, and more than 900 attendees overall, including families and caregivers. The scientific program featured 5 keynote lectures, 2 satellite meetings, 17 symposia, 7 nano symposia, 2 workshops, and 1 industry-focused session, totaling more than 150 oral presentations. More than 230 abstracts were presented as posters. The conference covered research across the lifespan of individuals with DS, spanning genomic and epigenetic regulation, molecular and cellular mechanisms, preclinical and experimental models, cognition and behavior, neurodevelopment, aging and neurodegeneration, co-occurring medical conditions, and therapeutic interventions. Dedicated sessions focused on capacity-building in DS research and societal engagement were established. Significantly, T21RS promoted inclusivity by supporting 60 young investigator fellowships, providing childcare awards, and organizing a two-day program for families and caregivers in collaboration with Italian DS associations. This proceeding summarizes the main scientific highlights of the 5th T21RS International Conference, reflecting the latest advances in DS biology, clinical research, biomarker development, and therapeutic innovation.

From kelp forests to turf reefs: Patterns, drivers, and impacts to functional diversity - Shane P. Farrell; Dara S. Yiu; Stuart K. Ryan; Rene D. Francolini; Courtney E. Stuart; Jonathan S. Lefcheck; Yasmina M. Shah Esmaeili; Douglas B. Rasher (Ecology, 2026)
Kelp forests are declining in many regions due to ocean warming, predator loss, and other anthropogenic stressors. In areas of rapid ocean warming, including the southern Gulf of Maine, these ecosystems have transitioned to a novel state dominated by low‐lying mats of turf algae. However, the pace, drivers, and ecological consequences of this transition remain unclear. Here, we used field surveys from 32 sites over 5 years (2018–2023) to reveal a continuation of kelp forest collapse and northward expansion of turf algae across Maine's coast. Next, we united data on benthic cover with key environmental variables in a structural equation model to show that turf algae were directly enhanced by higher ocean temperatures and decreased wave disturbance and indirectly enhanced by a warming‐induced loss of kelp cover. Lastly, we revealed the shift from kelp to turf yielded a seaweed assemblage dominated by traits associated with rapid growth, high surface area‐to‐volume ratios, and markedly reduced canopy height, indicating declines in habitat provisioning and carbon storage with kelp forest loss. Our findings highlight the accelerating impacts of climate change on temperate reef ecosystems and the vital services they provide. Further, we provide insights into a new state shift that is now occurring globally and underscore the need for urgent actions to mitigate further loss of foundational kelp forests.

RIFM fragrance ingredient safety assessment, phytyl acetate, CAS Registry Number 10236-16-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, [2,2-bis[(3,7-dimethyl-2,6-octadienyl)oxy]ethyl]benzene, CAS Registry Number 67634-02-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, 2,3,5,6-tetramethylpyrazine, CAS Registry Number 1124-11-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, cedryl methyl ether, CAS Registry Number 67874-81-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, methyl 2-(formylamino)benzoate, CAS Registry Number 41270-80-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, naphtho[2,1-b]furan, dodecahydro-3a,6,6,9a-tetramethyl-, (3aR,5aS,9aS,9bR)-, CAS Registry Number 6790-58-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, laurel leaf oil, CAS Registry Number 8007-48-5, RIFM ID 476-E2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, (Z)-2-penten-1-ol, CAS Registry Number 1576-95-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 6-methyl-3,5-heptadien-2-one, CAS Registry Number 1604-28-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, isopropylphenylbutanal, CAS Registry Number 125109-85-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, methyl cinnamate, CAS Registry Number 103-26-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, lovage leaf oil, CAS Registry Number 8016-31-7, RIFM ID 813-E2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, β,β,3-trimethyl benzenepropanol, CAS Registry Number 103694-68-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, dihydro-β-ionone, CAS registry number 17283-81-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 3-hexanone, CAS Registry Number 589-38-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, ethyl methylphenylglycidate, CAS Registry Number 77-83-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, dihydro-α-ionone, CAS Registry Number 31499-72-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, hinoki root oil, CAS Registry Number 91745-97-0, RIFM ID 5487-A2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, isobornyl methyl ether, CAS Registry Number 5331-32-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, ethyl safranate, CAS registry number 35044-57-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, Bucchu oil, betulina, CAS Registry Number 68650-46-4, RIFM ID 73-E2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, ethyl pyruvate, CAS registry number 617-35-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, thyme oil, red, CAS Registry Number 8007-46-3, RIFM ID 471.E2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, 2-methyl-3-tolylpropionaldehyde, CAS Registry Number 41496-43-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, dihydrocarvyl acetate, CAS Registry Number 20777-49-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 3,7-dimethyl-2,6-nonadien-1-al, CAS Registry Number 41448-29-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, isopulegyl acetate, CAS Registry number 57576-09-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, anisyl alcohol, CAS Registry Number 105-13-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, bicyclo[3.1.0]hexan-3-one, 4-methyl-1-(1-methylethyl)-, CAS Registry Number 1125-12-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 6-isopropyl-2(1H)-octahydronaphthalenone, CAS Registry Number 34131-98-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, ethyl 3-phenylglycidate, CAS Registry Number 121-39-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, citral, CAS Registry Number 5392-40-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 1,6-octadien-3-ol, 3,7-dimethyl-, acid-isomerized, CAS Registry Number 73018-51-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, 1,1-dimethoxycyclododecane, CAS Registry Number 950-33-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 2-ethyl-5-methoxybicyclo[2.2.1]heptane, CAS registry number 122795-41-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM natural complex substance (NCS) fragrance ingredient safety assessment, styrax absolute, CAS registry Number 8024-01-9, RIFM ID 6877.K2.1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, α,α-dimethyl-p-ethylphenylpropanal, CAS Registry Number 67634-15-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, α-hexylcinnamaldehyde, CAS Registry Number 101-86-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, γ-octalactone, CAS Registry number 104-50-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 4-methoxybenzoic acid, CAS Registry Number 100-09-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 3-methyl-2-butenyl acetate, CAS Registry Number 1191-16-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, γ-hexalactone, CAS Registry Number 695-06-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, myristic acid, CAS Registry Number 544-63-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, isobutyric acid, CAS Registry Number 79-31-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, γ-decalactone, CAS Registry Number 706-14-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, γ-undecalactone, CAS Registry Number 104-67-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, isovaleric acid, CAS Registry Number 503-74-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, γ-nonalactone, CAS Registry Number 104-61-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Peatland use and peat soil land cover types in Ireland: Implications for the calculation of GHG emissions in the context of climate action - L. Gilet; W. Habib; E. Aitova; K.A. Byrne; C.A. Farrell; O. Fenton; R. Flynn; D. O’Leary; T.R. Morley; P. Tuohy; S. Regan; F. Renou-Wilson; et al. (Land Use Policy, 2025)

2nd update to RIFM fragrance ingredient safety assessment, 3,7-dimethyl-1,6-nonadien-3-ol, CAS Registry Number 10339-55-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

2nd update to RIFM fragrance ingredient safety assessment, linalool, CAS Registry number 78-70-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2H-indeno[4,5b] furan, decahydro-2,2,6,6,7,8,8-heptamethyl, CAS Registry Number 476332-65-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, γ-dodecalactone, CAS Registry Number 2305-05-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, palmitic acid, CAS Registry number 57-10-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2,6,8-trimethylnonan-4-one, CAS Registry Number 123-18-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-methylbutyric acid, CAS Registry number 116-53-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 4,8-dimethyl-4,9-decadienal, CAS Registry number 71077-31-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, cedrene, CAS Registry Number 11028-42-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 5-methyl-3-heptanone, CAS Registry Number 541-85-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM natural complex substance (NCS) fragrance ingredient safety assessment, iris pallida oil, CAS registry number 8002-73-1, RIFM ID 265.A2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 8H-indeno(4,5-B)furan,2,3,3a,4,5,5a,6,7,8a,9-decahydro-2,6,6,7,8,8-hexamethyl mixture of isomers, CAS Registry Number 338735-71-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-nonanone, CAS Registry Number 821-55-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-undecanone, CAS Registry Number 112-12-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 3-octanone, CAS registry number 106-68-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-decanone, CAS Registry Number 693-54-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-heptanone, CAS Registry Number 110-43-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, γ-heptalactone, CAS Registry Number CAS # 105-21-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, γ-valerolactone, CAS Registry Number 108-29-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, lauric acid, CAS Registry Number 143-07-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-octanone, CAS Registry Number 111-13-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, benzoin infusion, Sumatra, CAS Registry Number 9000-05-9, RIFM ID 104-K2.31 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 4-heptanone, CAS Registry Number 123-19-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 3-heptanone, CAS Registry Number 106-35-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, myrtenol, CAS Registry Number 515-00-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 3-phenylpropionic acid, CAS registry number 501-52-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, hexyl phenylacetate, CAS Registry Number 5421-17-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, methyl cyclohexadiene (mixture of isomers), CAS Registry Number 30640-46-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, decanoic acid, CAS Registry Number 334-48-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 5-methyl-5-propyl-2-(1-methylbutyl)-1,3-dioxan, CAS Registry Number 80480-24-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, octanoic acid, CAS Registry Number 124-07-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, p-isopropylacetophenone, CAS Registry Number 645-13-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, nonanoic acid, CAS Registry Number 112-05-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 4H-4a,9-methanoazuleno[5,6-d]-1,3-dioxole, octahydro-2,2,5,8,8,9a-hexamethyl-, (4aR,5R,7aS,9R)-, CAS Registry Number 211299-54-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, spiro[5.5]undec-8-en-1-one, 2,2,7,9-tetramethyl-, CAS Registry Number 502847-01-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, p-tolyl 3-methylcrotonate, CAS Registry Number 24700-20-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, hexanoic acid, CAS Registry Number 142-62-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-methyl-4-phenyl-1,3-dioxolane, CAS Registry Number 33941-99-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-hydroxyacetophenone, CAS Registry Number CAS # 118-93-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 4-isopropyl-2-methoxy-1-methylbenzene, CAS Registry Number 6379-73-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 1-ethynylcyclohexyl acetate, CAS Registry Number 5240-32-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 4,4a,5,9b-tetrahydroindeno[1,2-d]-1,3-dioxine, CAS Registry Number 18096-62-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 3-phenyl-1-propanol, CAS Registry Number 122-97-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, benzaldehyde, CAS Registry Number 100-52-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Applications of vessel positional data in next-generation stock assessments - Chollett; S. O’Farrell; L. Perruso; S.R. Sagarese; C. Liese; K. Dettloff (Fisheries Research, 2025)

On the equatorial dayside ionosphere of Saturn – In-situ observations give evidence for a dynamic and layered structure in disequilibrium - J.-E. Wahlund; A.I. Eriksson; M.W. Morooka; S. Buchert; M. Persson; E. Vigren; J. Dreyer; W.S. Kurth; J.H. Jr Waite; J.-P. Lebreton; W.M. Farrell; I. Müller-Wodarg (Icarus, 2025)

RIFM fragrance ingredient safety assessment, benzeneacetonitrile, a-butylidene-, (Z), CAS Registry Number 130786-09-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, geraniol, CAS registry number 106-24-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-phenoxyethanol, CAS Registry number 122-99-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, cinnamyl alcohol, CAS Registry Number 104-54-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, benzyl alcohol, CAS Registry Number 100-51-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, benzoic acid, 2-[[3-(4-methoxyphenyl)-2-methylpropylidene]amino]-, methyl ester, CAS registry number 111753-62-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

2nd update to RIFM fragrance ingredient safety assessment, 4-carvomenthenol, CAS Registry Number 562-74-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 2-tert-butylcyclohexyl acetate, CAS registry number 88-41-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 3-tert-butylcyclohexyl acetate, CAS Registry Number 31846-06-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 4-tert-butylcyclohexyl acetate, CAS Registry Number 32210-23-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, phenyl salicylate, CAS Registry Number 118-55-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, fenchone, CAS Registry Number 1195-79-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, phenethyl acetate, CAS registry number 103-45-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, hydroxycitronellal diethyl acetal, CAS Registry Number 7779-94-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, amylcyclohexyl acetate (mixed isomers), CAS Registry Number 67874-72-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, octanal dimethyl acetal, CAS Registry Number 10022-28-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, linalyl hexanoate, CAS Registry Number 7779-23-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-methylundecanal dimethyl acetal, CAS Registry Number 68141-17-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, hydroxycitronellal dimethyl acetal, CAS Registry number 141-92-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 2-isobutylquinoline, CAS registry number 93-19-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 2-methyl quinoline, CAS registry number 91-63-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 1,1-diethoxyisooctane, CAS Registry Number 69178-43-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, nonane, 1,1-diethoxy-, CAS Registry Number 54815-13-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 1,1-diethoxy-3,5,5-trimethylhexane, CAS registry number 86198-35-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 2-(methylpropyl)quinoline, CAS registry number 1333-58-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, decanal dimethyl acetal, CAS Registry Number 7779-41-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 4-isopropylphenol, CAS Registry Number 99-89-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 3-buten-2-one, 4-(2,2,3-trimethyl-6-methylenecyclohexyl)-, CAS registry number 79-68-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, heptanal dimethyl acetal, CAS registry number 10032-05-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 1,1-diethoxyhexane, CAS registry number 3658-93-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 2-acetyl-5-methylfuran, CAS Registry Number 1193-79-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 2-furyl methyl ketone, CAS Registry Number 1192-62-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, savory winter oil, CAS Registry Number 90106-57-3, RIFM ID 1181-E2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM natural complex substance (NCS) fragrance ingredient safety assessment, ho wood oil, CAS Registry Number 8022-91-1, RIFM ID 217-D2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, dimethylcyclohex-3-ene-1-carbaldehyde (isomer unspecified), CAS Registry Number 27939-60-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 6-methyl-2-(4-methyl-3-cyclohexen-1-yl)-5-hepten-2-ol, CAS Registry Number 515-69-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, maltol, CAS registry number 118-71-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 3-(5,5,6-trimethylbicyclo[2.2.1]hept-2-yl)cyclohexan-1-ol, CAS registry number 3407-42-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, benzyl valerate, CAS Registry Number 10361-39-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isocyclocitral, CAS Registry Number 1335-66-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, ho leaf oil, CAS Registry Number 8022-91-1, RIFM ID 217-E2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM natural complex substance (NCS) fragrance ingredient safety assessment, ho bark oil, CAS registry number 8022-91-1, RIFM ID 217-C2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, benzyl formate, CAS Registry Number 104-57-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 1,1-diethoxyheptane, CAS Registry Number 688-82-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 1-octanol, CAS registry number 111-87-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 4,4a,6,7,8,8a-hexahydro-1,4-methanonaphthalen-5(1H)-one, CAS Registry Number 51519-65-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, amyl hexanoate, CAS registry number 540-07-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, N-benzoylanthranilic acid, CAS Registry Number 579-93-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, undecyl alcohol, CAS Registry Number 112-42-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 1-tridecanol, CAS Registry Number 112-70-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, lauryl alcohol, CAS Registry Number 112-53-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, hexyl alcohol, CAS Registry Number 111-27-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, ethyl maltol, CAS Registry Number 4940-11-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, butyrophenone, CAS Registry Number 495-40-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, p-tolyl phenylacetate, CAS Registry Number 101-94-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, methyl decanoate, CAS Registry Number 110-42-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 1-decanol, CAS registry number 112-30-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, nonyl alcohol, CAS Registry Number 143-08-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, methoxy dicyclopentadiene carboxaldehyde, CAS Registry Number 86803-90-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, octahydro-4,7-methano-1H-indenecarbaldehyde, CAS Registry Number 30772-79-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, acetophenone, CAS Registry number 98-86-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

2nd Update to RIFM fragrance ingredient safety assessment, α-amylcinnamaldehyde, CAS Registry Number 122-40-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, heptyl alcohol, CAS registry number 111-70-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 4-acetoxy-2,5-dimethyl-3(2H)furanone, CAS Registry Number 4166-20-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isoamyl propionate, CAS Registry Number 105-68-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isobutyl propionate, CAS Registry Number 540-42-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 4-(p-methoxyphenyl)-2-butanone, CAS Registry Number 104-20-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, cis-6-nonenal, CAS registry number 2277-19-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 3-phenylbutanal, CAS registry number 16251-77-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Linking functional responses and effects with stoichiometric traits - Eric K. Moody; Katie Anania; Kate S. Boersma; Tyler J. Butts; Jessica R. Corman; Spencer Cruz; W. Reilly Farrell; Kauan N. Fonseca; Amy C. Krist; Erin I. Larson; Alex Lewanski; Christian Liriano; et al. (Ecology, 2025)
Trait‐based approaches to study biodiversity responses to changing environmental conditions have become popular because these approaches provide context to how and why certain taxa shift in abundance within an assemblage. Trait‐based approaches also offer the potential to link shifts in assemblage composition to effects on ecosystem functions like rates of primary production, detrital decomposition, and nutrient uptake. However, focusing on response traits in multidimensional functional diversity studies limits our ability to make these linkages. We developed a multidimensional analytical and visual stoichiometric diversity framework that links organismal responses to and effects on environmental change using stoichiometric traits. We define these traits as the acquisition, assimilation, allocation, and excretion of key chemical elements by members of an assemblage. We discuss the considerations for using stoichiometric traits in a trait‐based framework and apply the framework to case studies of temporal variation in stream benthic invertebrate assemblages and spatial variation in urban woody vegetation assemblages. These examples illustrate the utility of the stoichiometric diversity framework for testing stoichiometric hypotheses and suggest promising linkages between assemblage shifts and shifts in ecosystem function.

Update to RIFM fragrance ingredient safety assessment, cyclohexanepropanol, α-ethyl-2,2,6-trimethyl-, CAS Registry Number 60241-52-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, cyclododecyl formate, CAS Registry Number 59052-82-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, (Z)-4-dodecenal, CAS registry number 21944-98-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-phenylpropionaldehyde, CAS registry number 93-53-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 4,5-dihydro-3(2H)thiophenone, CAS Registry Number 1003-04-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 9-undecenal, CAS Registry Number 143-14-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, β-methyl-benzenepentanal, CAS registry number 55066-49-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, trans-4-decen-1-al, CAS Registry Number 65405-70-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isoamyl formate, CAS Registry Number 110-45-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 8-undecenal, CAS registry number 58296-81-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 4-heptenal, CAS Registry Number 6728-31-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isoamyl alcohol, CAS Registry Number 123-51-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 3-methylbutyl valerate, CAS Registry Number 2050-09-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-methylbutyl butyrate, CAS Registry Number 51115-64-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, amyl alcohol, CAS Registry Number 71-41-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, pentanoic acid, 2-methylbutyl ester, CAS Registry Number 55590-83-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 3,4-xylenol, CAS Registry Number 95-65-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-methylbutyl acetate, CAS Registry Number 624-41-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isobutyl butyrate, CAS Registry Number 539-90-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, trans-2-hexenyl acetate, CAS Registry Number 2497-18-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, p-menth-8-en-2-one, CAS Registry Number 7764-50-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, l-menthyl (R,S)-3-hydroxybutyrate, CAS Registry Number 108766-16-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, butyl alcohol, CAS registry number 71-36-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 4′-tert-butyl-2′,6′-dimethylacetophenone, CAS Registry Number 2040-10-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, ethyl trans-2,cis-4-decadienoate, CAS registry number 3025-30-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isoamyl acetate, CAS Registry Number 123-92-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isobutyl acetate, CAS Registry Number 110-19-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isoamyl butyrate, CAS Registry Number 106-27-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, benzothiazole, CAS Registry Number 95-16-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 1-cyclopropylmethyl-4-methoxybenzene, CAS registry number 16510-27-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isobutyl alcohol, CAS Registry Number 78-83-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-methylpropyl pentanoate, CAS Registry Number 10588-10-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 3-methylbutanal diethyl acetal, CAS Registry Number 3842-03-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Review of APSIM's soil nitrogen modelling capability for agricultural systems analyses - Kirsten Verburg; Heather R. Pasley; Jody S. Biggs; Iris Vogeler; Enli Wang; Henrike Mielenz; Val O. Snow; Chris J. Smith; Chiara Pasut; Andrea D. Basche; Di He; Sotirios V. Archontoulis; et al. (Agricultural Systems, 2025)

Update to RIFM fragrance ingredient safety assessment, propyl alcohol, CAS Registry Number 71-23-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, β-ionyl acetate, CAS Registry Number 22030-19-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2,6-xylenol, CAS Registry Number 576-26-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, isobutyl formate, CAS registry number 542-55-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 4-(4,8-dimethylnona-3,7-dienyl)pyridine, CAS Registry Number 38462-23-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 1,3-propanediol, 2,2-dimethyl-, 1,3-diacetate, CAS registry number 13431-57-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 3-(cis-3-hexenyloxy)propanenitrile, CAS Registry Number 142653-61-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 4-(4-methyl-3-penten-1-yl)-2(5H)-furanone, CAS Registry number 61315-75-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2024)

Ritualized male–male combat resulting from intraspecific food competition in three Agkistrodon species - Terence M. Farrell; Henderson C. Gull; Frederick S. Boyce; Stephen C. Richter (Journal of Ethology, 2024)

A multinational survey of companion animal veterinary clinicians: How can antimicrobial stewardship guidelines be optimised for the target stakeholder? - S. Farrell; A.F. Bagcigil; S.C. Chaintoutis; C. Firth; F.G. Aydin; C. Hare; M. Maaland; A. Mateus; A.P. Vale; U. Windahl; P. Damborg; D. Timofte; et al. (The Veterinary Journal, 2024)

Importance of timely metadata curation to the global surveillance of genetic diversity - Eric D. Crandall; Rachel H. Toczydlowski; Libby Liggins; Ann E. Holmes; Maryam Ghoojaei; Michelle R. Gaither; Briana E. Wham; Andrea L. Pritt; Cory Noble; Tanner J. Anderson; Randi L. Barton; Justin T. Berg; et al. (Conservation Biology, 2023)
Genetic diversity within species represents a fundamental yet underappreciated level of biodiversity. Because genetic diversity can indicate species resilience to changing climate, its measurement is relevant to many national and global conservation policy targets. Many studies produce large amounts of genome‐scale genetic diversity data for wild populations, but most (87%) do not include the associated spatial and temporal metadata necessary for them to be reused in monitoring programs or for acknowledging the sovereignty of nations or Indigenous peoples. We undertook a distributed datathon to quantify the availability of these missing metadata and to test the hypothesis that their availability decays with time. We also worked to remediate missing metadata by extracting them from associated published papers, online repositories, and direct communication with authors. Starting with 848 candidate genomic data sets (reduced representation and whole genome) from the International Nucleotide Sequence Database Collaboration, we determined that 561 contained mostly samples from wild populations. We successfully restored spatiotemporal metadata for 78% of these 561 data sets ( n = 440 data sets with data on 45,105 individuals from 762 species in 17 phyla). Examining papers and online repositories was much more fruitful than contacting 351 authors, who replied to our email requests 45% of the time. Overall, 23% of our email queries to authors unearthed useful metadata. The probability of retrieving spatiotemporal metadata declined significantly as age of the data set increased. There was a 13.5% yearly decrease in metadata associated with published papers or online repositories and up to a 22% yearly decrease in metadata that were only available from authors. This rapid decay in metadata availability, mirrored in studies of other types of biological data, should motivate swift updates to data‐sharing policies and researcher practices to ensure that the valuable context provided by metadata is not lost to conservation science forever.

Evaluating species boundaries using coalescent delimitation in pine-killing Monochamus (Coleoptera: Cerambycidae) sawyer beetles - Patrick S. Gorring; Brian D. Farrell (Molecular Phylogenetics and Evolution, 2023)

Extreme eutrophication and salinisation in the Coorong estuarine-lagoon ecosystem of Australia's largest river basin (Murray-Darling) - L.M. Mosley; S. Priestley; J. Brookes; S. Dittmann; J. Farkaš; M. Farrell; A.J. Ferguson; M. Gibbs; M. Hipsey; J. Huang; O. Lam-Gordillo; S.L. Simpson; et al. (Marine Pollution Bulletin, 2023)

Millennial-scale drivers of small mammal isotopic niche dynamics in southern California - Nathaniel S. Fox; John R. Southon; Carrie M. Howard; Gary T. Takeuchi; Stephany Potze; Aisling B. Farrell; Emily L. Lindsey; Jessica L. Blois (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Using Protection Motivation Theory to Predict Intentions for Breast Cancer Risk Management: Intervention Mechanisms from a Randomized Controlled Trial - Claire C. Conley; Karen J. Wernli; Sarah Knerr; Tengfei Li; Kathleen Leppig; Kelly Ehrlich; David Farrell; Hongyuan Gao; Erin J. A. Bowles; Amanda L. Graham; George Luta; Jinani Jayasekera; et al. (Journal of Cancer Education, 2023)
The purpose of this study is to evaluate the direct and indirect effects of a web-based, Protection Motivation Theory (PMT)–informed breast cancer education and decision support tool on intentions for risk-reducing medication and breast MRI among high-risk women. Women with ≥ 1.67% 5-year breast cancer risk ( N = 995) were randomized to (1) control or (2) the PMT-informed intervention. Six weeks post-intervention, 924 (93% retention) self-reported PMT constructs and behavioral intentions. Bootstrapped mediations evaluated the direct effect of the intervention on behavioral intentions and the mediating role of PMT constructs. There was no direct intervention effect on intentions for risk-reducing medication or MRI ( p ’s ≥ 0.12). There were significant indirect effects on risk-reducing medication intentions via perceived risk, self-efficacy, and response efficacy, and on MRI intentions via perceived risk and response efficacy ( p ’s ≤ 0.04). The PMT-informed intervention effected behavioral intentions via perceived breast cancer risk, self-efficacy, and response efficacy. Future research should extend these findings from intentions to behavior. ClinicalTrials.gov Identifier: NCT03029286 (date of registration: January 24, 2017).

Stable carbon and nitrogen isotopes explain methylmercury concentrations in stream food webs of Lake George, New York (USA) - M. W. Swinton; P. K. Myer; M. F. Schaller; E. A. Pettitt; J. L. Farrell; S. A. Nierzwicki-Bauer (Ecotoxicology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Year-round acoustic monitoring of Antarctic blue and fin whales in relation to environmental conditions off the west coast of South Africa - Ishmail S. Letsheleha; Fannie W. Shabangu; Dara Farrell; Rex K. Andrew; Philip L. la Grange; Ken P. Findlay (Marine Biology, 2022)

Impacts of drought and native grass competition on buffelgrass (Pennisetum ciliare) - Hannah L. Farrell; Jennifer Funk; Darin Law; Elise S. Gornish (Biological Invasions, 2022)

Distant metastatic foci of infection in adult patients with diabetic foot – not as rare as we think?: case series and review of the literature - Mazen S. Bader; John Hawboldt; Yasmeen Vincent; Neal Irfan; Dominik Mertz; Alison Farrell; Annie Brooks (Infectious Diseases, 2021)

Advanced materials and technologies for supercapacitors used in energy conversion and storage: a review - M. I. A. Abdel Maksoud; Ramy Amer Fahim; Ahmed Esmail Shalan; M. Abd Elkodous; S. O. Olojede; Ahmed I. Osman; Charlie Farrell; Ala’a H. Al-Muhtaseb; A. S. Awed; A. H. Ashour; David W. Rooney (Environmental Chemistry Letters, 2021)
Supercapacitors are increasingly used for energy conversion and storage systems in sustainable nanotechnologies. Graphite is a conventional electrode utilized in Li-ion-based batteries, yet its specific capacitance of 372 mA h g −1 is not adequate for supercapacitor applications. Interest in supercapacitors is due to their high-energy capacity, storage for a shorter period and longer lifetime. This review compares the following materials used to fabricate supercapacitors: spinel ferrites, e.g., MFe 2 O 4 , MMoO 4 and MCo 2 O 4 where M denotes a transition metal ion; perovskite oxides; transition metals sulfides; carbon materials; and conducting polymers. The application window of perovskite can be controlled by cations in sublattice sites. Cations increase the specific capacitance because cations possess large orbital valence electrons which grow the oxygen vacancies. Electrodes made of transition metal sulfides, e.g., ZnCo 2 S 4 , display a high specific capacitance of 1269 F g −1 , which is four times higher than those of transition metals oxides, e.g., Zn–Co ferrite, of 296 F g −1 . This is explained by the low charge-transfer resistance and the high ion diffusion rate of transition metals sulfides. Composites made of magnetic oxides or transition metal sulfides with conducting polymers or carbon materials have the highest capacitance activity and cyclic stability. This is attributed to oxygen and sulfur active sites which foster electrolyte penetration during cycling, and, in turn, create new active sites.

Review of high dose vancomycin in the treatment of Clostridioides difficile infection - Mazen S. Bader; John Hawboldt; Cheryl Main; Dominik Mertz; Mark Loeb; Alison Farrell; Joanna Joyce (Infectious Diseases, 2020)

ACMT Position Statement: Medication Administration and Safety During the Response to COVID-19 Pandemic - Brenna M. Farmer; Jon B. Cole; Travis D. Olives; Natalija M. Farrell; Rama Rao; Lewis S. Nelson; Maryann Mazer-Amirshahi; Andrew I. Stolbach (Journal of Medical Toxicology, 2020)

Plastic Ingestion in Post-hatchling Sea Turtles: Assessing a Major Threat in Florida Near Shore Waters - Catherine B. Eastman; Jessica A. Farrell; Liam Whitmore; Devon R. Rollinson Ramia; Rachel S. Thomas; Jenifer Prine; Scott F. Eastman; Todd Z. Osborne; Mark Q. Martindale; David J. Duffy (Frontiers in Marine Science, 2020)

Assessing Chemical Mechanisms Underlying the Effects of Sunflower Pollen on a Gut Pathogen in Bumble Bees - Lynn S. Adler; Alison E. Fowler; Rosemary L. Malfi; Patrick R. Anderson; Lily M. Coppinger; Pheobe M. Deneen; Stephanie Lopez; Rebecca E. Irwin; Iain W. Farrell; Philip C. Stevenson (Journal of Chemical Ecology, 2020)

Mechanisms in mutualisms: a chemically mediated thrips pollination strategy in common elder - Alison S. Scott-Brown; Sarah E. J. Arnold; Geoffrey C. Kite; Iain W. Farrell; Dudley I. Farman; Dominique W. Collins; Philip C. Stevenson (Planta, 2019)

RGD-decorated cholesterol stabilized polyplexes for targeted siRNA delivery to glioblastoma cells - Bo Lou; Kate Connor; Kieron Sweeney; Ian S. Miller; Alice O’Farrell; Eduardo Ruiz-Hernandez; David M. Murray; Garry P. Duffy; Alan Wolfe; Enrico Mastrobattista; Annette T. Byrne; Wim E. Hennink (Drug Delivery and Translational Research, 2019)

Secondary metabolites from nectar and pollen: a resource for ecological and evolutionary studies - Evan C. Palmer‐Young; Iain W. Farrell; Lynn S. Adler; Nelson J. Milano; Paul A. Egan; Rebecca E. Irwin; Philip C. Stevenson (Ecology, 2019)
Floral chemistry mediates plant interactions with herbivores, pathogens, and pollinators. The chemistry of floral nectar and pollen, the primary food rewards for pollinators, can affect both plant reproduction and pollinator health. Although the existence and functional significance of nectar and pollen secondary metabolites has long been known, comprehensive quantitative characterizations of secondary chemistry exist for only a few species. Moreover, little is known about intraspecific variation in nectar and pollen chemical profiles. Because the ecological effects of secondary chemicals are dose‐dependent, heterogeneity across genotypes and populations could influence floral trait evolution and pollinator foraging ecology. To better understand within‐ and across‐species heterogeneity in nectar and pollen secondary chemistry, we undertook exhaustive LC ‐ MS and LC ‐ UV ‐based chemical characterizations of nectar and pollen methanol extracts from 31 cultivated and wild plant species. Nectar and pollen were collected from farms and natural areas in Massachusetts, Vermont, and California, USA , in 2013 and 2014. For wild species, we aimed to collect 10 samples from each of three sites. For agricultural and horticultural species, we aimed for 10 samples from each of three cultivars. Our data set (1,535 samples, 102 identified compounds) identifies and quantifies each compound recorded in methanolic extracts, and includes chemical metadata that describe the molecular mass, retention time, and chemical classification of each compound. A reference phylogeny is included for comparative analyses. We found that each species possessed a distinct chemical profile; moreover, within species, few compounds were found in both nectar and pollen. The most common secondary chemical classes were flavonoids, terpenoids, alkaloids and amines, and chlorogenic acids. The most common compounds were quercetin and kaempferol glycosides. Pollens contained high concentrations of hydroxycinnamoyl‐spermidine conjugates, mainly triscoumaroyl and trisferuloyl spermidine, found in 71% of species. When present, pollen alkaloids and spermidines had median nonzero concentrations of 23,000 μmol/L (median 52% of recorded micromolar composition). Although secondary chemistry was qualitatively consistent within each species and sample type, we found significant quantitative heterogeneity across cultivars and sites. These data provide a standard reference for future ecological and evolutionary research on nectar and pollen secondary chemistry, including its role in pollinator health and plant reproduction. Data are published under a Creative Commons Attribution License ( CC BY 3.0 US ) and may be freely used if properly cited.

Variation in Detrital Resource Stoichiometry Signals Differential Carbon to Nutrient Limitation for Stream Consumers Across Biomes - Kaitlin J. Farrell; Amy D. Rosemond; John S. Kominoski; Sophia M. Bonjour; Janine Rüegg; Lauren E. Koenig; Christina L. Baker; Matt T. Trentman; Tamara K. Harms; William H. McDowell (Ecosystems, 2018)

How the Comprehensive Cancer Control National Partnership shapes the public health workforce - Margaret M. Farrell; Kelsy M. Gibson; Angela Marler; Leslie Given; Aubrey Van Kirk Villalobos; Candace Deaton Maynard; Frank S. Bright; Ginny Thompson Kirklin; Truemenda C. Green; Melanie Ruhe; Julia Thorsness; Stephanie Weiss (Cancer Causes & Control, 2018)

Ameliorating the adverse cardiorespiratory effects of chemical immobilization by inducing general anaesthesia in sheep and goats: implications for physiological studies of large wild mammals - Adian Izwan; Edward P. Snelling; Roger S. Seymour; Leith C. R. Meyer; Andrea Fuller; Anna Haw; Duncan Mitchell; Anthony P. Farrell; Mary-Ann Costello; Shane K. Maloney (Journal of Comparative Physiology B, 2018)

A three‐phase excess post‐exercise oxygen consumption in Atlantic salmon Salmo salar and its response to exercise training - Y. Zhang; G. Claireaux; H. Takle; S. M. Jørgensen; A. P. Farrell (Journal of Fish Biology, 2018)
The recovery of oxygen uptake to the standard metabolic rate (SMR) following exhaustive chasing exercise in Atlantic salmon Salmo salar parr occurred in three phases (rapid, plateau and slow). The initial recovery phase lasted 0·7 h and contributed 16% to the total excess post‐exercise oxygen consumption (EPOC). It was followed by a longer plateau phase that contributed 53% to the total EPOC. The slow recovery phase that completed recovery of SMR, which has not been reported previously, made a 31% contribution to the total EPOC. The plasticity of EPOC was demonstrated in exercise‐trained fish. Exercise training increased EPOC by 39% when compared with control fish (mean ± S.E., 877·7 ± 73·1 v . 629·2 ± 53·4 mg O 2 kg −1 , d.f. = 9, P 0·05), with the duration of the plateau phase increasing by 38% (4·7 ± 0·58 v . 3·4 ± 0·16 h, d.f. = 9, P 0·05) and the contribution of the slow phase to the total EPOC increasing by 80% (173·9 ± 23·9 v . 312·5 ± 50·4 mg O 2 kg −1 , d.f. = 9, P v . 513·6 ± 43·1 mg O 2 kg −1 ; d.f. = 9, P = 0·01). To substantiate the hypothesis that the plateau and slow recovery phase of EPOC was related to general metabolic recovery following exhaustive exercise, the time‐course for recovery of SMR was compared with previously published metabolite recovery profiles. The final phase of metabolic recovery was temporally associated with the final phases of gluconeogenesis, lactate oxidation and muscle intracellular pH regulation. Therefore, the plasticity of the latter phase of EPOC agreed with the known effects of exercise training in fishes.

Adolescent cannabinoid exposure effects on natural reward seeking and learning in rats - H. Schoch; M. Y. Huerta; C. M. Ruiz; M. R. Farrell; K. M. Jung; J. J. Huang; R. R. Campbell; D. Piomelli; S. V. Mahler (Psychopharmacology, 2018)

Aging, frailty and complex networks - A. B. Mitnitski; A. D. Rutenberg; S. Farrell; K. Rockwood (Biogerontology, 2017)

Rapid Root Decomposition Decouples Root Length from Increased Soil C Following Grassland Invasion - Vasiliki G. Balogianni; Scott D. Wilson; Richard E. Farrell; Andrew S. MacDougall (Ecosystems, 2015)

Mouse genome annotation by the RefSeq project - Kelly M. McGarvey; Tamara Goldfarb; Eric Cox; Catherine M. Farrell; Tripti Gupta; Vinita S. Joardar; Vamsi K. Kodali; Michael R. Murphy; Nuala A. O’Leary; Shashikant Pujar; Bhanu Rajput; Sanjida H. Rangwala; et al. (Mammalian Genome, 2015)
Complete and accurate annotation of the mouse genome is critical to the advancement of research conducted on this important model organism. The National Center for Biotechnology Information (NCBI) develops and maintains many useful resources to assist the mouse research community. In particular, the reference sequence (RefSeq) database provides high-quality annotation of multiple mouse genome assemblies using a combinatorial approach that leverages computation, manual curation, and collaboration. Implementation of this conservative and rigorous approach, which focuses on representation of only full-length and non-redundant data, produces high-quality annotation products. RefSeq records explicitly link sequences to current knowledge in a timely manner, updating public records regularly and rapidly in response to nomenclature updates, addition of new relevant publications, collaborator discussion, and user feedback. Whole genome re-annotation is also conducted at least every 12–18 months, and often more frequently in response to assembly updates or availability of informative data. This article highlights key features and advantages of RefSeq genome annotation products and presents an overview of NCBI processes to generate these data. Further discussion of NCBI’s resources highlights useful features and the best methods for accessing our data.

Environmental conditions and physiological state influence estuarine movements of homing sockeye salmon - S. Matthew Drenner; Scott G. Hinch; Eduardo G. Martins; Nathan B. Furey; Timothy D. Clark; Steven J. Cooke; David A. Patterson; David Robichaud; David W. Welch; Anthony P. Farrell; Richard E. Thomson (Fisheries Oceanography, 2015)
The reproductive migration of anadromous salmonids through estuarine waters is one of the most challenging stages of their life cycle, yet little is known about the environmental and physiological conditions that influence migratory behaviour. We captured, sampled tissues, tagged and released 365 sockeye salmon ( Oncorhynchus nerka ) homing through inner coastal waters towards the Fraser River, British Columbia, Canada. Biotelemetry was used to assess the behaviour of individual sockeye salmon approaching estuarine waters and at river entry, which were related to both fish physiological condition at release and to prevailing environmental conditions. Sockeye salmon tended to stay close to the shore, migrated during the day, and movements were related to tide. Sockeye salmon migration rate was linked to wind‐induced currents, salinity and an individual's physiological state, but these factors were specific to location and stock. We propose that wind‐induced currents exposed sockeye salmon entering the estuary to stronger olfactory cues associated with Fraser River water, which in turn resulted in faster migration rates presumably due to either an increased ability for olfactory navigation and/or advanced reproductive schedule through a neuroendocrine response to olfactory cues. However, once the migration had progressed further into more concentrated freshwater of the river plume, sockeye salmon presumably used wind‐induced currents to aid in movements towards the river, which may be associated with energy conservation. Results from this study improve our biological understanding of the movements of Fraser River sockeye salmon and are also broadly relevant to other anadromous salmonids homing in marine environments.

Plant growth responses to biochar addition: an Australian soils perspective - Lynne M. Macdonald; Mark Farrell; Lukas Van Zwieten; Evelyn S. Krull (Biology and Fertility of Soils, 2014)

High water users can be drought tolerant: using physiological traits for green roof plant selection - Claire Farrell; Christopher Szota; Nicholas S. G. Williams; Stefan K. Arndt (Plant and Soil, 2013)

Low cardiac and aerobic scope in a coastal population of sockeye salmon Oncorhynchus nerka with a short upriver migration - E. J. Eliason; S. M. Wilson; A. P. Farrell; S. J. Cooke; S. G. Hinch (Journal of Fish Biology, 2013)
This study showed that a coastal population (Harrison) of Fraser River sockeye salmon Oncorhynchus nerka had a lower aerobic and cardiac scope compared with interior populations with more challenging upriver spawning migrations, providing additional support to the idea that Fraser River O. nerka populations have adapted physiologically to their local migratory environment.

Temporal and Spatial Patterns of Macroinvertebrates Associated with Small and Medium-Sized Free-Floating Plants - María S. Fontanarrosa; Griselda N. Chaparro; Inés O’Farrell (Wetlands, 2013)

Effects of exogenous abscisic acid and gibberellic acid on pre-maturity α-amylase formation in wheat grains - K. R. Kondhare; P. S. Kettlewell; A. D. Farrell; P. Hedden; J. M. Monaghan (Euphytica, 2012)

Dead fish swimming: a review of research on the early migration and high premature mortality in adult Fraser River sockeye salmon Oncorhynchus nerka - S. G. Hinch; S. J. Cooke; A. P. Farrell; K. M. Miller; M. Lapointe; D. A. Patterson (Journal of Fish Biology, 2012)
Adult sockeye salmon Oncorhynchus nerka destined for the Fraser River, British Columbia are some of the most economically important populations but changes in the timing of their homeward migration have led to management challenges and conservation concerns. After a directed migration from the open ocean to the coast, this group historically would mill just off shore for 3–6 weeks prior to migrating up the Fraser River. This milling behaviour changed abruptly in 1995 and thereafter, decreasing to only a few days in some years (termed early migration), with dramatic consequences that have necessitated risk‐averse management strategies. Early migrating fish consistently suffer extremely high mortality (exceeding 90% in some years) during freshwater migration and on spawning grounds prior to spawning. This synthesis examines multidisciplinary, collaborative research aimed at understanding what triggers early migration, why it results in high mortality, and how fisheries managers can utilize these scientific results. Tissue analyses from thousands of O. nerka captured along their migration trajectory from ocean to spawning grounds, including hundreds that were tracked with biotelemetry, have revealed that early migrants are more reproductively advanced and ill‐prepared for osmoregulatory transition upon their entry into fresh water. Gene array profiles indicate that many early migrants are also immunocompromised and stressed, carrying a genomic profile consistent with a viral infection. The causes of these physiological changes are still under investigation. Early migration brings O. nerka into the river when it is 3–6° C warmer than historical norms, which for some late‐run populations approaches or exceeds their critical maxima leading to the collapse of metabolic and cardiac scope, and mortality. As peak spawning dates have not changed, the surviving early migrants tend to mill in warm lakes near to spawning areas. These results in the accumulation of many more thermal units and longer exposures to freshwater diseases and parasites compared to fish that delay freshwater entry by milling in the cool ocean environment. Experiments have confirmed that thermally driven processes are a primary cause of mortality for early‐entry migrants. The Fraser River late‐run O. nerka early migration phenomenon illustrates the complex links that exist between salmonid physiology, behaviour and environment and the pivotal role that water temperature can have on population‐specific migration survival.

The effect of adrenaline on the temperature dependency of cardiac action potentials in pink salmon Oncorhynchus gorbuscha - S. Ballesta; L. M. Hanson; A. P. Farrell (Journal of Fish Biology, 2012)
Using sharp electrode impalement, action potentials recorded from atrial and ventricular tissue of pink salmon Oncorhynchus gorbuscha generally decreased in duration with increasing test temperature (6, 10, 16 and 20° C). Stimulation of the tissue using 500 nM adrenaline had no significant effect on the duration of the atrial action potential at any test temperature but lengthened the ventricular action potential by ∼17%.

Breeding for Bio-ethanol Production in Lolium perenne L.: Association of Allelic Variation with High Water-Soluble Carbohydrate Content - Kerrie Farrar; David N. Bryant; Lesley Turner; Joe A. Gallagher; Ann Thomas; Markku Farrell; Mervyn O. Humphreys; Iain S. Donnison (BioEnergy Research, 2012)

High-resolution array CGH defines critical regions and candidate genes for microcephaly, abnormalities of the corpus callosum, and seizure phenotypes in patients with microdeletions of 1q43q44 - Blake C. Ballif; Jill A. Rosenfeld; Ryan Traylor; Aaron Theisen; Patricia I. Bader; Roger L. Ladda; Susan L. Sell; Michelle Steinraths; Urvashi Surti; Marianne McGuire; Shelley Williams; Sandra A. Farrell; et al. (Human Genetics, 2012)

Physiological and molecular endocrine changes in maturing wild sockeye salmon, Oncorhynchus nerka, during ocean and river migration - A.-M. Flores; J. M. Shrimpton; D. A. Patterson; J. A. Hills; S. J. Cooke; T. Yada; S. Moriyama; S. G. Hinch; A. P. Farrell (Journal of Comparative Physiology B, 2012)

Silviculture and Forest Ecology - David Mercker; Ryan Blair; Don Tyler; Theresa Jain; Russell Graham; Donald Rockwood; Nicholas Koch; Jeremy Brawner; Omar Carrero; Kristofer Covey; Alex Barrett; Mark Ashton; et al. (Journal of Forestry, 2011)
2Over the past several decades, federal incentive programs have encouraged the restoration of bottomland forests throughout the West Gulf Coastal Plain (WGCP) and the Lower Mississippi Alluvial Valley (LMAV). Programs such as the Conservation Reserve (CRP) and Wetlands Reserve (WRP) Programs have been marginally successful (Stanturf et al. 2001). Foresters and contractors often follow conventional tree planting procedures that are well established for upland sites, but prove problematic in bottomlands. High water tables, soil drainage and compaction, overland flooding and diverse soil properties make species selection difficult. Slight changes in topography and soil structure often have a dramatic effect on survival and growth of planted oak seedlings (Hodges and Schweitzer 1979). This project documented the survival and growth of six-year old seedlings that were established on a bottomland site in 2004, located at the West Tennessee Research and Education Center, Jackson, Tennessee. The purpose was to determine how soil drainage as indicated by mottling (specifically, the point of 50 percent gray color throughout the soil profile) affects the survival and growth of bottomland oak species. The findings suggest that practitioners plant Nuttall, pin and overcup oaks in poorly drained soils. As the drainage improves, begin mixing in willow oak. In the best drained soils (if they exist), finish by including water, swamp chestnut, swamp white, Shumard, cherrybark and bur oaks. Potential species diversity should expand as the soil drainage improves.

Introduced and indigenous fungi of the Ross Island historic huts and pristine areas of Antarctica - R. L. Farrell; B. E. Arenz; S. M. Duncan; B. W. Held; J. A. Jurgens; R. A. Blanchette (Polar Biology, 2011)

The efficacy of field techniques for obtaining and storing blood samples from fishes - T. D. Clark; M. R. Donaldson; S. M. Drenner; S. G. Hinch; D. A. Patterson; J. Hills; V. Ives; J. J. Carter; S. J. Cooke; A. P. Farrell (Journal of Fish Biology, 2011)
Prompted by the dramatic increase in the use of blood analyses in fisheries research and monitoring, this study investigated the efficacy of common field techniques for sampling and storing blood from fishes. Three questions were addressed: (1) Do blood samples taken via rapid caudal puncture (the ‘grab‐and‐stab’ technique) yield similar results for live v. sacrificed groups of fishes? (2) Do rapidly obtained caudal blood samples accurately represent blood properties of fishes prior to capture? (3) Does storage of whole blood in an ice slurry for a working day (8·5 h) modify the properties of the plasma? It was shown that haematocrit, plasma ions, metabolites, stress hormones and sex hormones of caudal blood samples were statistically similar when taken from live v. recently sacrificed groups of adult coho salmon Oncorhynchus kisutch . Moreover, this study confirmed by using paired blood samples from cannulated O. kisutch that blood acquired through the caudal puncture technique (mean ± s.e . 142 ± 26 s after capture) was representative of fish prior to capture. Long‐term (8·5 h) cold storage of sockeye salmon Oncorhynchus nerka whole blood caused significant decreases in plasma potassium and chloride, and a significant increase in plasma glucose. Previous research has suggested that these changes largely result from net movements of ions and molecules between the plasma and erythrocytes, movements that can occur within minutes of storage. Thus, blood samples from fishes should be centrifuged as quickly as practicable in the field for separation of plasma and erythrocytes to prevent potentially misleading data.

Meningeal Coccidioidomycosis Diagnosed by Real-Time Polymerase Chain Reaction Analysis of Cerebrospinal Fluid - Matthew J. Binnicker; Alina S. Popa; Jelena Catania; Maria Alexov; Geoffrey Tsaras; Farrell Lloyd; Nancy L. Wengenack; Mark J. Enzler (Mycopathologia, 2011)

Reproductive biology of the starry smooth‐hound shark Mustelus asterias : geographic variation and implications for sustainable exploitation - E. D. Farrell; S. Mariani; M. W. Clarke (Journal of Fish Biology, 2010)
Examination of the reproductive biology of Mustelus asterias in the north‐east Atlantic Ocean highlighted apparent geographical variation in maturity, fecundity and ovarian cycle between Atlantic and Mediterranean populations. The stretch total length ( L ST ) and age at 50% maturity for Atlantic males and females were estimated at 78 cm L ST and 4–5 years and 87 cm L ST and 6 years, respectively. Size at maturity of females was considerably smaller than in Mediterranean specimens (96 cm L ST ). Ovarian fecundity ranged from eight to 27 oocytes and uterine fecundity from six to 18 embryos. The gestation period was c. 12 months, followed by a resting period of c. 12 months, resulting in a biennial cycle. Females stored sperm in the oviducal gland and, unlike Mediterranean specimens, no uterine compartments were observed in Atlantic specimens. This study reveals the existence of strong, possibly adaptive, divergence in life‐history traits in an elasmobranch, whose northern populations may be more susceptible to overexploitation than previously believed.

Zooplankton response to shading effects of free-floating plants in shallow warm temperate lakes: a field mesocosm experiment - M. S. Fontanarrosa; G. Chaparro; P. de Tezanos Pinto; P. Rodriguez; I. O’Farrell (Hydrobiologia, 2010)

Water-level regulation and coastal wetland vegetation in the upper St. Lawrence River: inferences from historical aerial imagery, seed banks, and Typha dynamics - John M. Farrell; Brent A. Murry; Donald J. Leopold; Alison Halpern; Molly Beland Rippke; Kevin S. Godwin; Sasha D. Hafner (Hydrobiologia, 2010)

Simultaneous biologging of heart rate and acceleration, and their relationships with energy expenditure in free-swimming sockeye salmon (Oncorhynchus nerka) - Timothy Darren Clark; E. Sandblom; S. G. Hinch; D. A. Patterson; P. B. Frappell; A. P. Farrell (Journal of Comparative Physiology B, 2010)

Testing the synergistic effects of GnRH and testosterone on the reproductive physiology of pre‐adult pink salmon Oncorhynchus gorbuscha - G. T. Crossin; S. G. Hinch; S. J. Cooke; D. A. Patterson; A. G. Lotto; G. Van Der Kraak; Y. Zohar; U. Klenke; A. P. Farrell (Journal of Fish Biology, 2010)
To test the hypothesis that the hypothalmic gonadotropin‐releasing hormone (GnRH) and testosterone (T) co‐treatment stimulates both the hypothalmo–pituitary–gonadal (HPG) and hypothalmo–pituitary–interrenal axes, the reproductive and osmoregulatory responses of pre‐adult pink salmon Oncorhynchus gorbuscha were compared after GnRH and T administration either alone or in combination. Relative to controls, neither GnRH nor T treatment resulted in significantly greater ovarian or testicular growth, but co‐treatment significantly increased ovarian growth after 5 months. Interestingly, the stimulation was undetectable after 3 months. However, once daily photoperiod began shortening after the summer solstice, c. 2 months before the natural spawning date, GnRH+T‐treated females were stimulated to produce larger ovaries. Final fish body length and the size of individual eggs did not differ among treatment groups. GnRH+T eggs, however, showed signs of advanced vitellogenesis relative to GnRH‐treated and control eggs, whereas T‐treated eggs became atretic. Testis size increased significantly from initial values and most males were spermiating, but this growth and development were independent of hormone treatments. Final plasma ion, metabolite and cortisol concentrations did not differ among treatment groups. It is concluded that GnRH+T co‐treatment was effective in stimulating female but not male maturation. GnRH and T treatment, however, presumably had little effect on the hypothalmo–pituitary–interrenal axis as observed by ionoregulatory status.

The relationship between grain weight and alpha-amylase in winter wheat: varietal comparison from UK field experiments - A. D. Farrell; P. S. Kettlewell (Euphytica, 2009)

Assessment of habitat and predator effects on dwarf rockfishes (Sebastes spp.) using multi model inference - Michael R. O’Farrell; Mary M. Yoklavich; Milton S. Love (Environmental Biology of Fishes, 2009)

Sex differences in circulatory oxygen transport parameters of sockeye salmon (Oncorhynchus nerka) on the spawning ground - Timothy Darren Clark; S. G. Hinch; B. D. Taylor; P. B. Frappell; A. P. Farrell (Journal of Comparative Physiology B, 2009)

Comparative expression and transcript initiation of three peach dehydrin genes - Carole Leavel Bassett; Michael E. Wisniewski; Timothy S. Artlip; Greg Richart; John L. Norelli; Robert E. Farrell (Planta, 2009)

Physiological, energetic and behavioural correlates of successful fishway passage of adult sockeye salmon Oncorhynchus nerka in the Seton River, British Columbia - L. B. Pon; S. G. Hinch; S. J. Cooke; D. A. Patterson; A. P. Farrell (Journal of Fish Biology, 2009)
Electromyogram (EMG) radio telemetry was used in conjunction with physiological biopsy to relate prior physiological condition and subsequent swimming energetics and behaviours to passage success of 13 wild adult sockeye salmon Oncorhynchus nerka at a vertical‐slot fishway on the Seton River, British Columbia. At the time of capture, plasma lactate, glucose and cortisol levels indicated that fish were not exhibiting unusually high levels of physiological stress. Very few differences existed between successful and unsuccessful fish in body size, initial plasma physiology and energy state and mean swim speed and energy use during passage. Generally, fish did not employ burst swimming during successful or failed attempts at passage, indicating that failure was probably not related to metabolic acidosis. Plasma Na + concentration was significantly lower in unsuccessful fish ( P O. nerka . Nevertheless, six of 13 fish failed to reascend the fishway and remained in the tailrace of the dam for more than a day on average before moving downstream and away from the dam. During this time, fish were observed actively seeking a means of passage, suggesting that there may have been other, undetermined causes of passage failure.

Rapid transcriptional response of apple to fire blight disease revealed by cDNA suppression subtractive hybridization analysis - John L. Norelli; Robert E. Farrell; Carole L. Bassett; Angela M. Baldo; Donna A. Lalli; Herb S. Aldwinckle; Michael E. Wisniewski (Tree Genetics & Genomes, 2009)

Calibration of a hand‐held haemoglobin analyser for use on fish blood - T. D. Clark; E. J. Eliason; E. Sandblom; S. G. Hinch; A. P. Farrell (Journal of Fish Biology, 2008)
The HemoCue haemoglobin analyser consistently overestimated haemoglobin concentration ([Hb]) in the blood of all fish species (sockeye salmon Oncorhynchus nerka , Chinook salmon Oncorhynchus tshawytscha , Pacific bluefin tuna Thunnus orientalis and chub mackerel Scomber japonicus ) by 22–50% (9·9–36·0 g l −1 ) over a [Hb] range of 20–160 g l −1 . The systematic nature of the overestimation, however, allowed the formulation of an accurate calibration equation that can be used to correct values of [Hb] measured by the HemoCue in field studies.

Air breathing minimizes post‐exercise lactate load in the tropical Pacific tarpon, Megalops cyprinoides Broussonet 1782 but oxygen debt is repaid by aquatic breathing - R. M. G. Wells; J. Baldwin; R. S. Seymour; K. A. Christian; A. P. Farrell (Journal of Fish Biology, 2007)
Swimming in a flume at reduced water pO 2 resulted in muscle and blood lactate levels in Pacific tarpon Megalops cyprinoides that were significantly higher when fish did not have access to air. Blood glucose and haematological variables were unchanged throughout the regimes of exercise at two swimming speeds and hypoxia. Strenuous exercise with bouts of burst swimming, however, resulted in both high blood lactate and glucose, and perturbed haematological status with elevated haemoglobin and reduced mean cell‐haemoglobin concentration. Post‐exercise recovery was achieved through aquatic breathing rather than by air breathing. The air‐breathing organ in Pacific tarpon therefore prolonged aerobic activity, but gill breathing was used to repay oxygen debt.

A novel technique for estimating the compact myocardium in fishes reveals surprising results for an athletic air‐breathing fish, the Pacific tarpon - A. P. Farrell; D. L. Simonot; R. S. Seymour; T. D. Clark (Journal of Fish Biology, 2007)
A method for quickly assessing the relative proportion of compact myocardium in the ventricle of teleosts is introduced and used in juvenile Pacific tarpon Megalops cyprinoides , a member of the only air‐breathing elopomorph teleost genus. The proportion of compact myocardium increased with body mass, reaching up to 60% of the ventricular mass. The finding for tarpon was a surprising discovery since recent literature has suggested that air breathing evolved primarily as means of supplying oxygen to the fish heart during activity. The present data, which represent the first quantitative assessment of the compact myocardium for any air‐breathing fish, suggest that myocardial oxygen supply in the tarpon is supplemented by the coronary circulation associated with compact myocardium during exercise, while air breathing is important during aquatic hypoxia. Compact myocardium was also measured as a point of reference in an extant representative from a more ancient fish lineage than the elopomorphs, the water‐breathing spiny dogfish Squalus acanthias and found to be only 9% of ventricular mass. In conclusion, the presence of a coronary circulation in extant elasmobranchs may mean that the coronary circulation evolved well before air breathing in fishes and, for tarpon at least, the coronary oxygen supply to the ventricular myocardium has not necessarily been superseded by air breathing.

Continuous measurement of oxygen tensions in the air-breathing organ of Pacific tarpon (Megalops cyprinoides) in relation to aquatic hypoxia and exercise - Roger S. Seymour; Anthony P. Farrell; Keith Christian; Timothy D. Clark; Michael B. Bennett; Rufus M. G. Wells; John Baldwin (Journal of Comparative Physiology B, 2007)

Fatigue is a behavioural response in respirometer‐confined smallmouth bass - S. J. Peake; A. P. Farrell (Journal of Fish Biology, 2006)
Fatigue in respirometer‐confined smallmouth bass Micropterus dolomieu was confirmed as being largely a behavioural response, and not brought about by depletion of anaerobic fuel stores. While data collected from these fish did not preclude the possibility that the behavioural response was triggered when some physiological threshold was exceeded, locomotory gait transition patterns in confined fish exposed to increasing water velocities support an alternate hypothesis. This is that fatigue is a behavioural decision made at (or near) the gait transition swimming speed, in an effort to avoid activity that, by virtue of the limited space in a typical respirometer, is energetically inefficient and biomechanically difficult.

Road Verge and Rangeland Plant Communities in the Southern Karoo: Exploring What Influences Diversity, Dominance and Cover - P. J. O’FARRELL; S. J. MILTON (Biodiversity and Conservation, 2006)

Acute Didecyl Dimethyl Ammonium Chloride Toxicity to Larval Lake Sturgeon, Acipenser fulvescens Rafinesque, Walleye Sander vitreus Mitchill, and Northern Pike, Esox lucius Linnaeus - M. A. Gray; S. J. Peake; A. P. Farrell; R. Bruch (Bulletin of Environmental Contamination and Toxicology, 2005)

Coupling non‐invasive physiological assessments with telemetry to understand inter‐individual variation in behaviour and survivorship of sockeye salmon: development and validation of a technique - S. J. Cooke; G. T. Crossin; D. A. Patterson; K. K. English; S. G. Hinch; J. L. Young; R. F. Alexander; M. C. Healey; G. Van Der Kraak; A. P. Farrell (Journal of Fish Biology, 2005)
Approximately 200 km from the mouth of the Fraser River, British Columbia, Canada, adult sockeye salmon Oncorhynchus nerka , were gastrically implanted with radio transmitters without anaesthetic. Subsets of the transmitter implanted fish were also biopsied which included drawing blood from the caudal peduncle (3 ml), removal of gill tissue (0·03 g) and quantification of energetic status using a microwave fat meter. Several experiments were used to test the hypothesis that the biopsy had a negligible effect on the subsequent survival and migratory behaviour of transmitter implanted fish. In the first experiment, no difference was found in the survival (both 100%) or tag retention (both 100%) between the two treatment groups (transmitter implanted with and without biopsy) when fish were held in pens for 24 h in the marine environment. Similarly, in other experiments where fish were released to the ocean to resume their migratory journey, no statistical differences were found in the travel times of fish in the two treatment groups, or in the proportion of fish that passed in‐river telemetry checkpoints. These results indicated that the handling and biopsy methods produced similar levels of mortality and tag retention as the telemetry treatment alone and that any changes in behaviour between the two treatment groups did not adversely affect migration time. Based upon the evidence provided from the biotelemetry of >300 adult sockeye salmon, it was felt that this general type of approach could be applicable to other fish species.

Effects of geometric isomerism in dinuclear platinum antitumor complexes on aquation reactions in the presence of perchlorate, acetate and phosphate - Junyong Zhang; Donald S. Thomas; Murray S. Davies; Susan J. Berners-Price; Nicholas Farrell (JBIC Journal of Biological Inorganic Chemistry, 2005)

Energetics and morphology of sockeye salmon: effects of upriver migratory distance and elevation - G. T. Crossin; S. G. Hinch; A. P. Farrell; D. A. Higgs; A. G. Lotto; J. D. Oakes; M. C. Healey (Journal of Fish Biology, 2004)
Depending on population, wild Fraser River sockeye salmon Oncorhynchus nerka travel distances of 1100 km and ascend elevations ranging from near sea‐level to 1200 m to reach spawning areas. Populations embarking on distant, high elevation migrations ( i.e . Early Stuart, Chilko and Horsefly populations) began their upriver spawning migrations with higher densities of somatic energy ( c . 9·2 to 9·8 MJ kg −1 ) and fewer eggs ( c . 3200 to 3800) than populations making shorter, low elevation migrations ( i.e . Weaver and Adams; c . 7·1 to 8·3 MJ kg −1 gross somatic energy and c . 4300 to 4700 eggs). Populations making difficult upriver migrations also had morphologies that were smaller and more fusiform than populations making less difficult migrations, traits that may facilitate somatic energy conservation by reducing transport costs. Indeed, fish travelling long distances expended less somatic energy per unit of migratory difficulty than those travelling shorter distances (2·8 to 3·8 kJ v . 10–1400 kJ). Consistent with evolutionary theory, difficult migrations appear to select for energy efficiency but ultimately fish making more difficult migrations produce fewer eggs, even when differences in body length have been accounted for. Despite large among‐population differences in somatic energy at the start of upriver migration, all populations completed migration and spawning, and subsequently died, with c . 4 MJ kg −1 of energy remaining, a level which may reflect a threshold to sustain life.

The effect of temperature and acclimation period on repeat swimming performance in cutthroat trout - M. J. MacNutt; S. G. Hinch; A. P. Farrell; S. Topp (Journal of Fish Biology, 2004)
Hatchery cutthroat trout Oncorhynchus clarki clarki were used to examine the effects of 48 h and 3 week temperature acclimation periods on critical swimming speed ( U crit ). The U crit was determined for fish at acclimation temperatures of 7, 14 and 18° C using two consecutive ramp‐ U crit tests in mobile Brett‐type swim tunnels. An additional group was tested at the stock's ambient rearing temperature of 10° C. The length of the temperature acclimation period had no significant effect on either the first or the second U crit ( U crit‐1 and U crit‐2 , respectively) or on the recovery ratio (the quotient of U crit‐2 U crit‐1 −1 ). As anticipated, there was a significant positive relationship between U crit‐1 and temperature ( P U crit‐2 and temperature ( P = 0·10). Acclimation temperature had no significant effect ( P = 0·71) on the recovery ratio. These results indicate that a 48 h acclimation to experimental temperatures within the range of −3 to +8° C of the acclimation temperature may be sufficient in studies of swimming performance with this species. This ability to acclimate rapidly is probably adaptive for cutthroat trout and other species that occupy thermally variable environments.

The effect of exercise and captivity on energy partitioning, reproductive maturation and fertilization success in adult sockeye salmon - D. A. Patterson; J. S. Macdonald; S. G. Hinch; M. C. Healey; A. P. Farrell (Journal of Fish Biology, 2004)
Releasing a population of adult Fraser River sockeye salmon Oncorhynchus nerka from an energetically more expensive non‐feeding natural migration (1089 km, natal groups) and allowing them to sexually mature in either a moderate flow (captive exercise group) or a no flow (captive non‐exercise group) environment resulted in significant differences in body energy densities (MJ kg −1 ) among groups (ranked: initial natural migrator > non‐exercise > exercise > natal arrivals). Similarly, per cent body lipids were significantly lower in exercise females compared with non‐exercise females, experimentally confirming the central role lipid catabolism has in powering swimming. Although restricting exercise did result in greater body energy reserves at spawning, this did not result in a reallocation of energy to reproduction, as fecundity, egg size and gonad composition were unchanged among the groups. Furthermore, non‐exercise females had delayed maturity, lower egg deposition rates, and were more likely to die prior to egg ovulation than exercise females and natal spawners. Eggs from captive exercise adult females were more likely to survive to the eyed stage than eggs from captive non‐exercise females, but both captive groups had significantly lower egg fertilization success than natal spawners suggesting that confinement stress played a role in some of results presented. There were no significant differences in plasma levels of glucose, lactate, cortisol and reproductive hormones among the groups, but correlations among acute and chronic indicators of stress were significant among individuals. These results indicate that exercise during the late stages of maturation, as might occur normally, may be required for optimizing reproductive maturation and maximizing reproductive success.

Synteny between a major heading-date QTL in perennial ryegrass (Lolium perenne L.) and the Hd3 heading-date locus in rice - I. P. Armstead; L. B. Turner; M. Farrell; L. Skøt; P. Gomez; T. Montoya; I. S. Donnison; I. P. King; M. O. Humphreys (Theoretical and Applied Genetics, 2004)

Field‐based measurements of oxygen uptake and swimming performance with adult Pacific salmon using a mobile respirometer swim tunnel - A. P. Farrell; C. G. Lee; K. Tierney; A. Hodaly; S. Clutterham; M. Healey; S. Hinch; A. Lotto (Journal of Fish Biology, 2003)
Novel field measurements of critical swimming speed ( U crit ) and oxygen uptake ( M o 2 ) in three species of adult Pacific salmon Oncorhynchus spp. up to 3·5 kg in body mass were made using two newly designed, mobile Brett‐type swim tunnel respirometers sited at a number of field locations in British Columbia, Canada. Measurements of U crit , which ranged from 1· 68 to 2·17 body lengths s −1 , and maximum M o 2 , which ranged from 8·74 to 12·63 mg O 2 kg −1 min −1 depending on the species and field location, were judged to be of similar quality when compared with available data for laboratory‐based studies. Therefore high quality respirometry studies were possible in the field using adult wild swimming salmonids. In addition, the recovery of wild adult Pacific salmon from the exhaustive U crit swim test was sufficiently rapid that swimming performance could be repeated with M o 2 being reestablished. This result suggests that wild adult salmon are capable of carrying a moderate excess post‐exercise oxygen consumption without adversely affecting U crit , maximum M o 2 or swimming economy. Such capabilities may be extremely important for timely migratory passages when salmonids face repetitive hydraulic challenges on their upstream migration.

Comparison of results from several AOGCMs for global and regional sea-level change 1900-2100 - J. M. Gregory; J. A. Church; G. J. Boer; K. W. Dixon; G. M. Flato; D. R. Jackett; J. A. Lowe; S. P. O'Farrell; E. Roeckner; G. L. Russell; R. J. Stouffer; M. Winton (Climate Dynamics, 2001)

Sulfur K-edge XANES study of local electronic structure in ternary monosulfide solid solution [(Fe, Co, Ni) 0.923 S] - S. P. Farrell; M. E. Fleet (Physics and Chemistry of Minerals, 2001)

National Survey of Hepatitis Testing and Vaccination Services Provided by Drug Services in England and Wales - A. J. Winstock; J. Sheridan; S. Lovell; M. Farrell; J. Strang (European Journal of Clinical Microbiology & Infectious Diseases, 2000)

Metal Analysis of Scales Taken from Arctic Grayling - A. P. Farrell; A. H. Hodaly; S. Wang (Archives of Environmental Contamination and Toxicology, 2000)

Gastrointestinal blood flow in the red Irish lord, Hemilepidotus hemilepidotus : long-term effects of feeding and adrenergic control - M. Axelsson; H. Thorarensen; A. P. (Tony) Farrell; S. Nilsson (Journal of Comparative Physiology B, 2000)

Acute hormonal responses to heavy resistance exercise in younger and older men - William J. Kraemer; Keijo Hkkinen; Robert U. Newton; Matthew McCormick; Bradley C. Nindl; Jeff S. Volek; Lincoln A. Gotshalk; Steven J. Fleck; Wayne W. Campbell; Scott E. Gordon; Peter A. Farrell; William J. Evans (European Journal of Applied Physiology, 1998)